CHEK1 and GFPT1 as Potential Blood-Based Biomarkers for Colorectal Cancer - Habibah Faroque; Nur Soleha Aria; Nor Amira Muzilah; Hamid Ali Nagi Al-Jamal; Mohd Fadliyazid Ab. Rahim; Yasuhiro Nakamura; Hironobu Sasano; Abdullah Azmahani (Indonesian Biomedical Journal, 2023)
BACKGROUND: The checkpoint kinase 1 (CHEK1) and glutamine-fructose-6-phosphate aminotransferase 1 (GFPT1) genes have been reported to have a crucial role in carcinogenesis in colorectal cancer (CRC). However, their association with the pathogenesis of CRC remains unclear. This study was conducted to study the expression of CHEK1 and GFPT1 genes in adenoma and adenocarcinoma CRC patients’ whole blood samples compared to the healthy controls.